Build back better the case of GMA Kapuso Village, Tacloban City - Piñon, Meryl Louise P.; Silvio, Mecerna Mae D.; Torres, Kristine Mae (2016)
Super typhoon Yolanda (international name: Haiyan), the strongest tropical cyclone to ever hit land in recorded history, made its way to the Philippines on November 8, 2013. It triggered heavy rains and strong winds that caused widespread flooding, landslides, and even storm surges. The lack of power and communication in the provinces affected by the typhoon drove a lot of Filipino families to flee their homes, trying their very best to escape the horror that they have experienced. The catastrophe has affected more than one million families, an estimated number of 6,300 casualties, 28,689 injured victims and 1,061 missing individuals. National authorities indicated that the typhoon likely caused the most significant damage in the Philippines' Eastern Samar and Leyte provinces, with additional damages reported in Bohol, Cebu, and Samar provinces.